Assessment of tumor volume and density as a measure of the response of advanced hepatocellular carcinoma to sorafenib: Application of automated measurements on computed tomography scans. Issue 2 (2nd August 2019) - Yamamichi, Junta; Kawaguchi, Yasunori; Otsuka, Taiga; Nakashita, Shunya; Mizobe, Hideaki; Eguchi, Yuichiro; Kimura, Shinya
Abstract : Background and Aim: To better predict patient survival, we used automated tumor volume and density measurements to make an objective radiological assessment of the response of advanced hepatocellular carcinoma (HCC) to treatment with sorafenib. Methods: Patients treated with sorafenib were identified retrospectively. Those who were diagnosed with Child‐Pugh class A liver function, Barcelona‐Clinic Liver Cancer stage C, and Eastern Cooperative Oncology Group performance status grade 0/1 were enrolled ( n = 22). Reviews of contrast‐enhanced computed tomography images were supported by the automated measurement of lesions using computer software. Treatment responses were assessed using volume and density criteria. Kaplan–Meier methods and multivariate Cox regression analysis were used to evaluate treatment responses and identify the most significant prognostic factors for overall survival (OS). Results: After patients were dichotomized according to volume and density criteria, the median OS for those with an objective response (OR) (complete response + partial response) was 20.4 months and that for those with a non‐OR (stable disease + progressive disease) was 9.3 months ( P = 0.009). The best multivariate regression model for survival identified volume and density criteria (OR or non‐OR) as a significant variable, along with baseline alpha‐fetoprotein levels (log‐rank test, P = 0.01). No other conventional criteria were identified as significant. Conclusions: Tumor volume and density assessment using automated lesion measurements may be an objective method of evaluating responses of advanced HCC to treatment with sorafenib. Abstract : Tumor volume and density assessment using automated lesion measurements may be an objective method of evaluating the responses of advanced hepatocellular carcinoma to treatment with sorafenib.